ТӨРИЙН БОДЛОГЫН ҮЙЛ ЯВЦ ДАХЬ ИРГЭДИЙН ОРОЛЦООНЫ ЗАРИМ АСУУДАЛ /1990 ОНООС ХОЙШ/ - Ц.Ганболд; Н.Мягмарцоож (Politology, 2023)
The study is based on modern conception mentioning that all stages of public policy development demand citizen’s participation. Based on current context, Mongolian citizen’s meaningful participation in public policy development is at starting point. There is lack of effective practices and supportive culture of civic participation at all government structure. The vertical system of Mongolian governance is creates negative impacts to of citizen’s participation in public policy development. Top-down approach (Government to citizens) has more chance comparing with down-top approach (civil society to Government). Web forums, open discussions and Civic Hall these are just some examples of citizen’s participation in policy development process. In other ways, it is always lack of citizen’s participation in evaluation of policy implementation. This may result to lose its systematic approach of civic participation. There is no existing mechanism which supports information flows lead to citizens. Especially, monitoring and evaluation organizations are not supportive to culture of civic participation. Based on these arguments, the study has been sharing the 3 main recommendations: 1. Enabling policy and legislative environment 2. Developing supportive structures and institutions 3. Enhancing management of partnership with citizens